Die verband tussen gesin-van-oorsprongfaktore en huweliksbevrediging - Groenewald, Anja (University of the Free State, 2005)
The recent paradigm shift towards Positive Psyc hology emphasizes psychological wellbeing and the factors that promote wellbeing. Marital satisfaction is seen as an important determinant of a person’s general wellbeing (Larson & Holman, 1994, Ryff, 1995). Therefore, in striving for wellbeing and happiness, it would be important to determine which factors influence marital satisfaction. One of the factors that are studied in relation to marital satisfaction is the families -of-origin of the marital partners. It is generally accepted that individuals are shaped by their experiences within their original families (Bartle -Haring & Sabatelli, 1998; Freeman, 1992). This study investigated the relationship between the level of marital satisfaction of married couples in their middle adult years and their family-of-origin factors. Consequently the research type is non-experimental. Firstly the relationship between the couples’ (husbands and wives combined) level of marital satisfaction and their own family-of -origin factors were investigated. These relationships for husbands and wives were also investigated independently. Secondly the relationship between the husband’s family-of-origin factors and the wife’s level of marital satisfaction, and the wife’s family -of-origin factors and the husband’s level of marital satisfaction were investigated. The Marital Adjustment Test of Locke and Wallace (1959) was used to measure marital satisfaction. The items of this test comprise several dimensions of marital functioning (Schutte & Molouff, 1995). The McMaster Family Assessment Device was used to measure family -of-origin functioning within six areas: problem solving, communication, roles, affective responsivity, affective involvement and behavior control (Epstein & Bishop, 1991). This instrument also has a general functioning scale. A snowball sample consisting of 47 couples were obtained. The sample population was a homogenous group of Afrikaans -speaking married couples with at least one child. Both marital partners had to be between the age of 29 and 40. After obtaining the results it also became evident that the group consisted mainly of well-schooled individuals. 71 persons’ (75,5% of the total group) jobs were professional, semi-professional, technical, managing, executive or administrative in nature. The instruments are self-report questionnaires. In this study a relationship was found between the family -of-origin factor ‘roles’ and marital satisfaction. Roles also account for a significant part of the variance in marital satisfaction in middle adulthood. If roles were clearly defined and well allocated within the family-of-origin, that person’s marital satisfaction would be higher. Affective responsivity also correlates with marital satisfaction. If an individual learned within his/her family-of -origin to express a variety of emotions appropriately, it could contribute to his/her marital satisfaction. A relationship was found between the wife’s family-of-origin factor roles and her own marital satisfaction. Both roles and affective involvement account for a significant part of the variance in the wife’s marital satisfaction. The greater the extent to which her family-of-origin was interested in her and her activities, the greater her marital satisfaction. Lastly, the wife’s family-of-origin factor roles correlated with the husband’s marital satisfaction. This study contributed to the research by identifying factors that can promote marital satisfaction and wellbeing. The importance of the family-of-origin, especially with regard to a woman’s marital satisfaction, was highlighted. A big gap exists concerning the studying of family-of-origin factors in South-African marriages, while research abroad clearly indicates that these factors can not be ignored anymore (Doucet & Aseltine, 2003; Larson & Holman, 1994).
Dissertation (M.A. (Counselling Psychology))--University of the Free State, 2005
Keywords: Families -- Psychological aspects; Middle adulthood; Locke Wallace Marital Adjustment Test; McMaster Family Assessment Device; Roles; Affective responsibility; Affective involvement; Family-of-origin; Marital satisfaction; Well-being